2022
DOI: 10.1097/j.pain.0000000000002751
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and sex-specific expression of mu opioid receptors in anterior cingulate and somatosensory S1 cortical areas

Abstract: Supplemental Digital Content is Available in the Text.Pain-processing anterior cingulate and primary somatosensory cortical areas display distinct MOR expression profiles with prominent differences between output layers and sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…In addition, we confirmed that the astrocytic MOR in MOR-mCherry mice functions normally, as evidenced by the DAMGOinduced glutamate release in hippocampal astrocytes. This functional result is consistent with the previous evidence of intact MOR functionality in the MOR-mCherry reporter mouse which has shown normal expression, trafficking, TREK-1 colocalization, and MOR-mediated behavior responses [5,14,15]. We suggested the possibility that the expression of astrocytic MOR exhibits sex-differences in the brain regions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we confirmed that the astrocytic MOR in MOR-mCherry mice functions normally, as evidenced by the DAMGOinduced glutamate release in hippocampal astrocytes. This functional result is consistent with the previous evidence of intact MOR functionality in the MOR-mCherry reporter mouse which has shown normal expression, trafficking, TREK-1 colocalization, and MOR-mediated behavior responses [5,14,15]. We suggested the possibility that the expression of astrocytic MOR exhibits sex-differences in the brain regions.…”
Section: Discussionsupporting
confidence: 92%
“…The Oprm1 tm4Kff reporter mouse line (MOR-mCherry) [ 14 - 16 ], in which mCherry is tagged to the C-terminus of MOR, has been widely utilized to investigate MOR expression in neurons, due to the advantages of the unique transgenic property. Furthermore, this mouse line has confirmed the remaining functional MOR characteristics in MOR-mCherry mice, including normal Oprm1 gene transcription, proper distribution and trafficking of MOR-mCherry, comparable MOR agonist binding and potency, and conditioned place preference and pain-related behavioral responses as similar as observed in the wild-type mouse ( Oprm1 +/+ ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly relevant for depression is the processing of both physical and psychological pain, where the ACC is relevant for the affective component [ 39 ]. The primary somatosensory cortex, on the other hand, is associated with the sensory-discriminative component [ 39 ] and increased rsFC between the thalamus and the SSC has been found in MDD, as compared to HC, which correlates with core symptom severity of MDD, such as cognitive dysfunction, anhedonia, etc. [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prominent finding in our research is the involvement of the anterior cingulate cortex (ACC) and more specifically the subcallosal area as well as the postcentral gyrus as differentiating components for MDD. The ACC has an extensive functional capacity with processing the affective component of pain ( 62 ) which is one of the more relevant in terms of the clinical presentation of depression. The postcentral gyrus, on the other hand, has been linked with the sensory-discriminative component of pain.…”
Section: Discussionmentioning
confidence: 99%